Rare location of Universal tumor - Bastakoti, Shankar; Shrestha, Amar; Gautam, Dej Kumar; Bhatta, Ranjan Raj (Nepalese Journal of Cancer, 2021)
Lipomas are one of the most common benign mesenchymal tumor in human. Lipoma occurring in the tongue is rare as tongue has paucity of normal adipose tissue. Here we present an unusual case of lipoma presented in the tongue, and removal of which comforted patient by regaining of the functional task of tongue. Fifty two year’s old Muslim women presented with painless swelling on right lateral border of tongue for 5 years for which excision was done and histopathology evaluation was performed. The histopathology was consistent with the diagnosis of Lingual Lipoma. Existence of lipoma in the tongue is very rare, which can be managed by simple excision. Histopathology is the gold standard in the diagnosis.